(untitled) (Al-Academy, 2025)
Contemporary Iraqi art has a new conceptual and aesthetic value in all its attachments, proposals, and uses, and in the fields of art that constitute an inevitable release of continuous travails, conflicts, and transformations with its political, economic, social, and cultural pressures that constitute a displacement at the level of vision, taste, and reception in contemporary Iraqi art.The current research (objectification in contemporary Iraqi art) has sought to study the system of relationships, according to the mechanisms of their operation in art. The research included four chapters: The first chapter was concerned with the research framework, which deals with the problem of the research, its importance and the need for it, and the current research objectives represented by: defining reification in contemporary Iraqi art according to its works in it, as well as the limits of the research (2013-2013). The first chapter ended by defining the most important terms included in the research. The second chapter included: two sections representing the theoretical framework and its indicators as a culmination of previous studies. The first section dealt with: reification philosophically... and the second section dealt with: the emergence of contemporary Iraqi painting. The study ends with indicators of the theoretical framework and a presentation of previous studies that formed similarities and differences with the research topic. As for the third chapter: it included the research procedures, by defining the research community and its representative sample, ending with the analysis of the research sample of (3) samples distributed according to the time period, in addition to the research tool, which took indicators as a methodological basis in its formulation. After it was presented to a group of specialized experts, and after it gained apparent validity, it was prepared for analysis according to the mechanisms stated in it. The fourth chapter included a number of results and conclusions, as well as a number of recommendations and proposals. Among the most important results reached by the researcher: 1- The volumetricity of human forms constituted the largest space for constructing apparent objectivity and its implicit concept in artistic productions. 2- The apparent forms gave objectification to man’s individuality through the breadth of his imagination in building his emotional artistic composition. Among the most important conclusions reached by the researcher: 1- The internal conflict of a person crystallizes within the self in areas that are larger as a result of those pressures to depict something in a larger area. 2- The individual human feeling acts as a product of forms that are built in the artist’s imagination, and he installs them to depict the cumulative acquisition in expressing their content.